Explicit versus implicit motivations: Clarifying how experiences affect turkey hunter satisfaction using revised importance-performance, importance grid, and penalty-reward-contrast analyses. Issue 1 (2nd January 2018) - Schroeder, Susan A.; Cornicelli, Louis; Fulton, David C.; Merchant, Steven S.
ABSTRACT: Although research has advanced methods for clarifying factors that relate to customer satisfaction, they have not been embraced by leisure researchers. Using results from a survey of wild turkey hunters, we applied traditional and revised importance-performance (IPA/RIPA), importance-grid analysis (IGA), and penalty-reward-contrast analysis (PRCA) to examine how activity-specific factors influenced satisfaction. Results suggested differences between the explicit and implicit importance of factors related to turkey hunting. Opportunities to kill turkeys were explicitly rated as less important than seeing, hearing, or calling in turkeys, but opportunities for harvest had relatively higher levels of implicit importance. PRCA identified "calling turkeys in" and "hearing gobbling" as minimum requirements that cause dissatisfaction if not fulfilled, but do not provide satisfaction, whereas "seeing turkeys" and an "opportunity to kill a turkey" related to both satisfaction and dissatisfaction. RIPA, IGA, and PRCA could provide valuable insights about factors that may improve satisfaction for leisure participants.